Penggunaan Instagram Sebagai Media Konseling Islam: Content Analisys Pada Akun Instagram @shiftmedia.id - Jasman, Jasman; Mizkazola, Indri; Maiseptian, Fadil (Jurnal Kajian dan Pengembangan Umat, 2024)
This research is motivated by the use of Instagram as a medium for Islamic counseling on the @shiftmedia.id account. Based on the analysis carried out, it shows that the implementation of Islamic da'wah and counseling is not only focused on face-to-face meetings, but can be carried out through social media. The aim of this research is to describe the use of Instagram as a medium for Islamic counseling in disseminating Islamic information and Islamic education. The research method used is qualitative with a content analysis design. The data source in this research is secondary data with documentation and information obtained from written sources or documents. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this research from Islamic information show that uploaded posts have Islamic counseling values such as self-control, therapy for health, feeling sympathy and empathy, good ethics and mental therapy. As for Islamic education, Instagram is a supporting medium for providing lessons and teaching to someone. The value of Islamic counseling contained in it is teaching to be physically and mentally healthy, increasing faith and perfecting worship of Allah SWT.